Accident or osteoporosis?: Survey of community follow-up after low-trauma fracture - Singh, Sonia (College of Family Physicians of Canada, 2011)
OBJECTIVE: To describe the postfracture osteoporosis management of at-risk patients presenting with low-trauma fracture in a suburban community hospital setting. DESIGN: Telephone survey. SETTING: Hospital emergency department serving a retirement community in White Rock and South Surrey, BC. PARTICIPANTS: Men and women older than 40 years of age who presented with low-trauma fracture between October 1, 2004, and April 30, 2005. MAIN OUTCOME MEASURES: The prevalence of bone mineral density testing, osteoporosis medication prescriptions, referrals to fall prevention programs, and calcium and vitamin D supplementation within 6 months of the index fracture, as well as patient perceptions of future risk of fracture and sources of osteoporosis information. RESULTS: A total of 181 people met the eligibility criteria and 161 were contacted; 84 (52%) people responded, of whom 53 were interviewed. At the time of their index fractures, 79% (42 of 53) of patients surveyed were not taking osteoporosis medication. After the index fracture, 30% (16 of 53) received new bone mineral density testing, and 8% (4 of 53) were starting courses of new osteoporosis medication. Sixty-eight percent (36 of 53) of all patients were taking calcium supplements and 50% (26 of 53) were taking vitamin D supplements. Eight percent (4 of 53) of patients were referred to a fall prevention program and 9% (5 of 53) were prescribed hip protectors; 19% (10 of 53) of patients thought they were at risk of having another fracture. CONCLUSION: Osteoporosis management of patients after low-trauma fracture in this community was suboptimal; the role of the media, family and friends, and allied health professionals to prevent fractures in at-risk individuals needs to be further explored.